Cornflake Madu & Kuih Nestum / Muhammad Syafiq Izzuddin Samsul Buhari - Samsul Buhari, Muhammad Syafiq Izzuddin (2021)
This social media portfolio is one of the assignments for principles of entrepreneurship (ENT530). For this assignment, I need to create a business and do promoting the business by using social media platform. As per requested, I choose to make business that related to the food because as we know our Raya celebration will come which is Cornflake Madu & Kuih Nestum. Cornflake Madu & Kuih Nestum is made by me and my mom. Our business located at Rawang, Selangor because it such a great location since it crowded with people around here. It could bring a lot of profits to my business because it easy for them to reach our product and choose what they wants based on the design that have been exposed. My target customer is for those who have an active lifestyle and make a good appearance in public. My business promoting this Cornflake Madu and Kuih Nestum through Facebook page (FB). This page help boost my business profits and gained a lot of attention from our customers.